2022
DOI: 10.1002/1878-0261.13316
|View full text |Cite
|
Sign up to set email alerts
|

Cancer as an infective disease: the role of EVs in tumorigenesis

Abstract: Cancer is conventionally considered an evolutionary disease where tumor cells adapt to the environment and evolve eventually leading to the formation of metastasis through the seeding and growth of metastasis-initiating cells in distant organs. Tumor cell and tumor-stroma communication via soluble factors and extracellular vesicles (EVs) are essential for the success of the metastatic process. As the field of EVs advances, growing data support the role of tumor-derived EVs not only in modifying the microenviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 201 publications
0
4
0
Order By: Relevance
“…Their role in cancerous processes has notably received particular attention, enabling the scientific community to unravel the mechanisms of exosome capture and action. At the same time, the communication system driven by EVs in cancer revealed an extreme complexity of both pro- and anti-tumor effects [ 100 , 101 , 102 ]. For example, EVs derived from malignant cells, which differ in content from exosomes produced by healthy cells, have been shown to play a key role in liver pre-metastatic niche initiation during pancreatic cancer [ 58 , 59 ].…”
Section: Exosomes Are Small Specialized Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Their role in cancerous processes has notably received particular attention, enabling the scientific community to unravel the mechanisms of exosome capture and action. At the same time, the communication system driven by EVs in cancer revealed an extreme complexity of both pro- and anti-tumor effects [ 100 , 101 , 102 ]. For example, EVs derived from malignant cells, which differ in content from exosomes produced by healthy cells, have been shown to play a key role in liver pre-metastatic niche initiation during pancreatic cancer [ 58 , 59 ].…”
Section: Exosomes Are Small Specialized Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…In addition to the contribution of BMDCs to the generation of pre-metastatic niches, multiple studies have identified a large number of cytokines, chemokines, and growth factors which are connected to specific pre-metastatic niche-related processes [ 171 , 172 , 173 ]. In recent studies, EVs secreted from primary tumor cells have been described to have unique and central functions during PMN establishment and maintenance [ 174 , 175 , 176 ].…”
Section: Extracellular Vesicle-mediated Pre-metastatic Niche Formationmentioning
confidence: 99%
“…On the other hand, the transfer of oncogenic nucleic acids such as miRNAs, specifically miR-221 from highly aggressive breast tumor cells to nonaggressive cancer cells, via EVs, contributing to the promotion of epithelial-to-mesenchymal transition (EMT) [ 71 ] and leading to the induction of proliferation and metastasis while preventing drug-induced apoptosis of EVs’ fused recipient cells [ 5 ]. Therefore, tumor cells more often induce oncogenic transformations into normal healthy cells via the transfer of oncogenic bioactive molecules through EVs [ 72 , 73 ].…”
Section: Tumor-derived Evsmentioning
confidence: 99%